2010
DOI: 10.1007/978-3-642-13281-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Laser Processing Architecture for Improved Material Processing

Abstract: This chapter presents a novel architecture and software-hardware design system for materials processing techniques that are widely applicable to laser directwrite patterning tools. This new laser material processing approach has been crafted by association with the genome and genotype concepts, where predetermined and prescribed laser pulse scripts are synchronously linked with the tool path geometry, and each concatenated pulse sequence is intended to induce a specific material transformation event and thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, by altering the protocol of the crystalline growth process, we have shown that a different phase of the lithium silicate could also be formed that show velocity changes (i.e., Δυ S , Δυ L ) of over 11% and 9%, respectively. Finally, by implementing laser amplitude modulation and the use of specific pulse sequence profiles, it becomes possible to pattern both the LMS and LDS phases on the same sample and thereby allow sections to be removed by chemical etching and sections to remain for controlling the propagation of ultrasonic waves. It also becomes feasible to engineer the propagation of mechanical force through a material where Poisson’s ratio can be varied locally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, by altering the protocol of the crystalline growth process, we have shown that a different phase of the lithium silicate could also be formed that show velocity changes (i.e., Δυ S , Δυ L ) of over 11% and 9%, respectively. Finally, by implementing laser amplitude modulation and the use of specific pulse sequence profiles, it becomes possible to pattern both the LMS and LDS phases on the same sample and thereby allow sections to be removed by chemical etching and sections to remain for controlling the propagation of ultrasonic waves. It also becomes feasible to engineer the propagation of mechanical force through a material where Poisson’s ratio can be varied locally.…”
Section: Discussionmentioning
confidence: 99%
“…Variability of exposure, resulting from the changing velocity of the motion stages, is reduced because the prescribed exposure dose is defined in terms of net distance traveled rather than specific time duration. 23 Each 1 cm × 1 cm pattern is exposed at constant laser power even though it is possible to vary this by amplitude modulating the EO crystal. However, laser power changes between square pattern exposures are automatically changed by altering the voltage amplitude on the EO crystal (i.e., the light valve).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A solution to this third problem, which surprisingly has not been implemented, is the synchronous amplitude modulation of the laser/energy source with the motion platform. 9 Moreover, the development of an optical spectroscopy system can be complex if information on the scale of tens of microns is necessary from a distance of tens centimeters.…”
Section: Introductionmentioning
confidence: 99%